Composition and source determination of heavy metals (HM) in particles in selected primary schools in Pahang - Zahaba, Maryam; Abdul Hadi, Hazrin; Ariffin, Hizzri; Abdull, Norhidayah; Samsuddin, Niza; Mohd Aris, Mohd Shukri (Universiti Teknologi MARA (UiTM) Pulau Pinang, 2017)
Composition and concentrations of air pollutants in particles have been shown to have a correlation with differences in mortality counts in different parts of the world. These particles are also able to deteriorate health especially the respiratory system and may lead to mortality. Toxic metals in these particles are associated with respiratory diseases and lung cancer in school children. The effects of HM toxicity are more severe to the schoolchildren as their immune system is not fully developed yet. Thus, this study aims to analyse the HM composition in particles collected inside the classroom during the school days (occupied) and the weekends (vacant), and to determine pattern of HM concentration from particles based on different location backgrounds (residential, industrial and rural). In order to achieve these objectives, the following samplings were done. The particles were simultaneously collected using GilAir-5 air pump sampler (Sensidyne, USA) inside and outside the classrooms. The sampling was done for a minimum of 8 hours. The exposed Mixed Cellulose Ester (MCE) membrane filters (0.8µm, 37 mm) were digested following the International Standard Test Method (ASTM) for Determination of Elements in Airborne Particulate Matter by Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). The compositions of metals in particles were determined using ICP-MS NexION™ 300× (PerkinElmer, USA). From the result obtained, concentration of Al, Zn and Pb inside the classrooms were higher compared to the other elements like Cr, Mg, Cd and Cu. Meanwhile, HM concentration detected in the industrial site was higher compared to the residential and rural sites.